Antioxidant Capacity Fraction of the Pelawan Stems (Tristaniopsis merguensis Griff) - Mahardika, Robby Gus; Fajri, Khairul; Henri, Henri (Indonesian Journal of Chemical Research, 2023)
The impact of reactions free radical compounds can cause various health problems such as inflammation, aging, and cancer. Therefore, to avoid damage caused by free radicals, the body needs an important substance, antioxidants. Natural antioxidants are more recommended than synthetic antioxidants because synthetic antioxidants must be in accordance with the prescribed dose because they can cause side effects that are harmful to the body. This study aimed to determine the antioxidant activity of the extract and fraction of the Pelawan (Tristaniopsis merguensis Grifft.) stem extract. Antioxidant testing was carried out using the DPPH method on extracts and fractions of Pelawan stem extract (T. merguensis Grifft.). In addition, qualitative phytochemical testing was also carried out on extracts of the stems of Pelawan (T. merguensis). The results of the three solvent fractions, n-hexane, ethyl acetate, and methanol, were positive for flavonoid and phenolic secondary metabolites. Meanwhile, the antioxidant activity in reducing DPPH radicals in the methanol extract fraction of pelawan stems had a very strong activity with an IC50 value of 36.33 g/mL, while the ethyl acetate and n-hexane extract fractions had a very weak antioxidant activity with an IC50 value of 387.43 μg/mL dan 759.88 μg/mL.